Pengaruh Konsumsi Timun dan Bawang Merah terhadap Penurunan Kadar Kolesterol Pasien di Wilayah Kerja Puskesmas Babakan - Nandini, Ni Kadek; Zaetun, Siti; Inayati, Nurul; Lale Budi Kusuma Dewi (Journal of Indonesia Laboratory Students (JILTS), 2024)
Hypercholesterolemia is caused by the liver not being able to control LDL in the blood vessels, this condition will cause atherosclerosis and cardiovascular disease. Sterols and flavonoids are content that found in cucumbers which can lower cholesterol by replacing sterols with LDL which will be absorbed in the digestive system. The LDL will be excreted in the form of feces with the help of flavonoids And quercetin is a content found in red onions that can reduce cholesterol levels in the blood by inhibiting the HMG Co-A reductase enzyme. Yankestrad is a program at the Babakan Public Health Center include the use of medicinal plants (TOGA) such as cucumbers and red onions. The purpose of this study is to know the effect of cucumber and red onions consumption on reducing cholesterol levels in patients in the Babakan Health Center work area through the Yankestrad program. Research methods are analytical observational with case control research design and purposive sampling methods. The results of this there is an effect of consuming cucumber and red onions on reducing cholesterol levels.